Convenience behavior in German university students is associated with sociodemographic, study- and health-related factors - Lisa Schwab; Jennifer L. Reichel; Antonia M. Werner; Markus Schäfer; Sebastian Heller; Dennis Edelmann; Manfred E. Beutel; Stephan Letzel; Pavel Dietz; Perikles Simon; Kristin Kalo (Frontiers Media S.A., 2024)
BackgroundThe transition from school to university is often accompanied by a change in students' lifestyles. So far little is known whether convenience behavior is an essential factor affecting students' health and social interaction. In a heterogeneous population regard to sociodemographic and anthropometric characteristics the Convenience Behavior Questionnaire (CBQ) showed a better relationship between convenience-related behavior with overweight and obesity than established questionnaires. Here we assessed convenience behavior in a large well characterized cohort of university students and its association with health-related (mainly sedentary behavior and physical activity), study-related and sociodemographic factors with the Convenience Behavior Questionnaire (CBQ).MethodsA total of 4,351 students participated in an online survey, of which 3,983 (23.6 ± 5.3 years old, 71.3% females) answered the questions concerning convenience behavior. A low value in the CBQ indicates more convenience behavior [Convenience Behavior Index (CBI) range: 3-15]. Differences with regard to sociodemographic (age, gender, body mass index), study-related (semester, degree, field of study) and health-related (physical activity, sedentary behavior) variables were examined with Mann-Whitney-U test or Kruskal-Wallis test and post-hoc tests (Bonferroni).ResultsThe CBI of men and women differed significantly (z = −6.847, p < 0.001, r = 0.11). First-year students and students beyond their first year showed significant differences (z = −2.355, p ≤ 0.05, r = 0.04). Differences were also found in the field of study (Chi2 (6) = 147.830, p < 0.001) and the targeted degree (Chi2 (7) = 79.985, p < 0.001). Furthermore, differences were found in the body mass index (Chi2 (5) = 70.678, p < 0.001), physical activity (Chi2 (2) = 279.040, p < 0.001) and sedentary behavior (z = −4.660, p < 0.001, r = 0.07).ConclusionThe results showed risk groups of convenience behavior among students [men, first-year, students enrolled in "Science, Technology, Engineering and Mathematics (STEM)," bachelor]. Our results confirm for the first time in a very homogeneous population a gender difference and an association between CBI and health-related factors. Further studies are needed to analyze the health behavior of students in more detail, especially their convenience behavior.